LIPOSOMES CONTAINING PHYTOCHEMICALS FOR CANCER TREATMENT-AN UPDATE - Khan, Yunus Y.; Suvarna, Vasanti (International Journal of Current Pharmaceutical Research, 2016)
Many phytochemicals exhibit promising effects in treatment and prevention of various cancers, but due to their poor water solubility, stability, bio-availability and target specificity make administering them at therapeutic doses impractical. This is especially true for curcumin, quercetin, resveratrol and berberine. There is rising activity in developing nano drug delivery systems for these phytochemicals. These nano drug delivery systems mainly include liposomes, micelles, solid lipid nanoparticles, nanoemulsions, which are biocompatible and biodegradable nanoparticles. These nanoparticles can increase the stability and aqueous solubility of phytochemicals. They can also be used as sustained drug delivery systems. Much work has also proven that they enhance the absorption and bioavailability of the phytochemicals, protect them from premature enzymatic degradation or metabolism, hence prolonging their circulation time. Besides these parameters, in this review, we have also mentioned the improved target specificity of phytochemicals to cancer cells or tumours via passive or targeted delivery. Hence, nanotechnology cleared the way for developing phytochemical-loaded nanoparticles for prevention and treatment of cancer.